2015
DOI: 10.1007/s11571-015-9339-z
|View full text |Cite
|
Sign up to set email alerts
|

The electrocortical modulation effects of different emotion regulation strategies

Abstract: The current event-related potential study investigated the modulation effects of different emotion regulation strategies on electrocortical responses. When watching negative or neutral pictures, participants were instructed to perform three tasks: cognitive reappraisal, expressive suppression and passive viewing. We found that negative pictures elicited a larger late positive potential (LPP) than neutral pictures. Moreover, processes involved in strategy also had an effect on LPP amplitude, which was indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 55 publications
3
20
0
Order By: Relevance
“…Thus, when comparing the impact of the emotional content on the stimuli in the distancing vs. attend condition, one may immediately note the drastic LPP reduction (left-posterior region, first time window [250–400 ms]: effect of emotional content (negative—neutral) in the REGULATE condition: 0.79 μV vs. effect of emotional content (negative—neutral) in the Attend condition: 1.74 μV; second time window [400 600 ms]: effect of emotional content (negative—neutral) in the REGULATE condition: 0.21 μV vs. effect of emotional content (negative—neutral) in the Attend condition: 1.36 μV). Previous studies using ERPs reported that the LPP amplitude is affected by instructions to down-regulate the emotional responses due to negative stimuli [12,20,21,55,56,60]. These studies involved participants using cognitive strategies such as reappraisal, suppression and distraction, and showed regulation of both subjective ratings and LPP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, when comparing the impact of the emotional content on the stimuli in the distancing vs. attend condition, one may immediately note the drastic LPP reduction (left-posterior region, first time window [250–400 ms]: effect of emotional content (negative—neutral) in the REGULATE condition: 0.79 μV vs. effect of emotional content (negative—neutral) in the Attend condition: 1.74 μV; second time window [400 600 ms]: effect of emotional content (negative—neutral) in the REGULATE condition: 0.21 μV vs. effect of emotional content (negative—neutral) in the Attend condition: 1.36 μV). Previous studies using ERPs reported that the LPP amplitude is affected by instructions to down-regulate the emotional responses due to negative stimuli [12,20,21,55,56,60]. These studies involved participants using cognitive strategies such as reappraisal, suppression and distraction, and showed regulation of both subjective ratings and LPP.…”
Section: Discussionmentioning
confidence: 99%
“…Paul et al [20] showed a reduction of LPP when participants used distraction and reappraisal-based strategies. Gan and colleagues [21] replicated the effect of reduction of emotion enhanced LPP when participants applied reappraisal and observed an increase of N2 for the suppression strategy, possibly related to the control of facial expression. More recently, Qi et al [22] used detached reappraisal (similar to what we indicate with the term distancing) to regulate unpleasant pictures and reported a modulation of LPP.…”
Section: Introductionmentioning
confidence: 96%
“…Our study confirms this modulation of LPP as an effect of down-regulating the content of emotional pictures (significant difference in the central line electrodes), especially in the first stages of the component (i.e., between 250 ms and 600 ms after target presentation), that showed the maximal LPP reduction at multiple sites. Thus, when comparing the impact of the emotional content on the stimuli in the distancing vs. attend condition, one may immediately note ERPs reported that the LPP amplitude is affected by instructions to down-regulate the emotional responses due to negative stimuli [12,20,21,55,56,60]. These studies involved participants using cognitive strategies such as reappraisal, suppression and distraction, and showed regulation of both subjective ratings and LPP.…”
Section: Discussionmentioning
confidence: 99%
“…Paul et al, [20] showed a reduction of LPP when participants used distraction and reappraisal-based strategies. Gan and colleagues [21] replicated the effect of reduction of emotion Emotion regulation and ERP enhanced LPP when participants applied reappraisal and observed an increase of N2 for the suppression strategy, possibly related to the control of facial expression. More recently, Qi et al, [22], used detached reappraisal (similar to what we indicate with the term distancing) to regulate unpleasant pictures and reported a modulation of LPP.…”
Section: Introductionmentioning
confidence: 87%
“…In passive picture viewing paradigms, the N2 has been associated to stimulus discrimination, the automatic evaluation of affective valence, and arousal 27 28 . Another recent study found that N2 amplitudes were associated with the suppression of the emotional response while viewing neutral and negative pictures, which the authors interpreted as an indicator of conflict 29 . However, with regard to the processing of food stimuli, anterior negative deflections in the N2 time-range in two studies showed that higher amplitudes were related to an increased reactivity to food stimuli 30 31 .…”
mentioning
confidence: 96%